Murder city: the bloody history of Chicago in the twenties - Lesy, Michael (Norton, 2007)
Carl Wanderer -- Cora Isabelle Orthwein -- Harvey Church -- Catherwood -- Roach and Mosby -- Arthur, Eleanor, and Kate -- The banker -- Leighton Mount -- Fred-Frances -- Duffy double murder -- Belva and Beulah -- Assassins -- Hymie Weiss -- Christ's dream -- Diamond Joe -- Pearl -- Three murders